Dynamic Investment Models and the Firm's Financial Policy - Bond, S.; Meghir, C. (Review of Economic Studies, 1994)
In this paper we investigate the sensitivity of investment to the availability of internal funds using the hierarchy of finance approach to corporate finance. We characterize the empirical implications of this approach for dynamic investment models and test these implications using firm-level data. The model we estimate is based on the Euler equation for optimal capital accumulation in the presence of convex adjustment costs. The theoretical model explicitly allows for debt finance and financial assets. The empirical investigation uses U.K. company panel data to estimate dynamic investment models using GMM and tests the derived implications.